Immunological Effects of Recombinant Lactobacillus casei Expressing IHNV G Protein and Rainbow Trout (Oncorhynchus mykiss) Chemokine CK6 as an Oral Vaccine - Sun, Jinhui; Zhang, Mengmeng; Zhao, Dandan; Yang, Jiawei; Shi, Yanxue; Xu, Baoxing; Liu, Xuefei; Guan, Xueting; Shi, Wen; Liu, Min (Frontiers in Immunology, 2022)
IHNV is a virus that causes serious economic damage to salmonids. There is no specific medicine for the disease caused by this pathogen and the main preventive measure is vaccination but only for small groups of individuals. Therefore, it is important to investigate new oral vaccines to prevent and treat IHNV. In this study, the CK6 chemokine protein of rainbow trout and the IHNV truncated G protein were used to construct a secretory expression recombinant L.casei immunization with rainbow trout. The results showed that the levels of IgM and IgT antibodies in rainbow trout reached the highest level on the 15th day after the secondary immunization, and the antibodies had the highest inhibitory activity against viral infection. It was also found that pPG-612-CK6-G/L.casei 393 could stimulate splenic lymphocyte proliferation and improve mucosal immunity with significant differences compared to the control group. When infected with IHNV, the protection rate of pPG-612-CK6-G/L.casei 393 was 66.67% higher than that of the control group. It can be seen that pPG-612-CK6-G/L.casei 393 secreted expressing the rainbow trout chemokine CK6 protein and IHNV truncated G protein retained the original immunogenicity while enhancing the survival rate of rainbow trout. This indicates that recombinant L.casei provides a theoretical basis and rationale for the development of an oral vaccine against IHNV and has important practical implications for the protection of rainbow trout from IHNV infection.